Marshall or Jacobs? Answers to an unsuitable question from an interaction model - Jan Kluge; Robert Lehmann (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
This paper investigates whether localization economies as brought forward by Marshall(1890) or urbanization economies as mentioned by Jacobs (1970) are more decisive forregional gross value added per capita. Our novel approach is to explicitly allow forinterdependencies between these two theories and to take into account that the initiallevels of specialization and diversification might play a role. We therefore deploy amodel with interaction terms and find that these two theories are not mutually exclusivein most of our sectors. In addition, the empirical results show that the initial levels ofspecialization and diversification do matter as well.
Keywords: C33; O18; O40; R11; 330; Localization and urbanization economies; interaction models; regional gross valued added; Regionales Cluster; Agglomerationseffekt; Räumliche Interaktion; Regionale Entwicklung; Wertschöpfung; Theorie